Potentiation of imatinib by cilostazol in sensitive and resistant gastrointestinal stromal tumor cell lines involves YAP inhibition - Vandenberghe, Pierre (Oncotarget, 2019)
Despite the introduction of tyrosine kinase inhibitors, gastrointestinal stromal tumors (GIST) resistance remains a major clinical challenge. We previously identified phosphodiesterase 3A (PDE3A) as a potential therapeutic target expressed in most GIST. The PDE3 inhibitor cilostazol reduced cell viability and synergized with the tyrosine kinase inhibitor imatinib (Gleevec™) in the imatinib-sensitive GIST882 cell line. Here, we found that cilostazol potentiated imatinib also in the imatinib-resistant GIST48 cell line. Cilostazol induced nuclear exclusion, hence inactivation, of the transcriptional co-activator YAP, in a cAMP-independent manner. Verteporfin, a YAP/TEAD interaction inhibitor, reduced by 90% the viability of both GIST882 and GIST48 cells. Our results highlight the potential use of compounds targeting PDE3A or YAP in combined multitherapy to tackle GIST resistance.